The CredibleMeds® list: Usage of QT interval prolonging drugs in Germany and discordances with prescribing information. Issue 1 (13th July 2021) - Then, Melanie I.; Andrikyan, Wahram; Maas, Renke; Fromm, Martin F.
Abstract : Aims: A substantial number of Summaries of Product Characteristics (SmPCs)/Prescribing Information (PI) have warnings or contraindications on QT interval prolongation. The goal of this work was to quantify usage of QT interval prolonging drugs according to the CredibleMeds ® database of the German outpatient drug prescription market and to evaluate discrepancies between German SmPCs/US PI and CredibleMeds ® . Methods: Drugs listed on CredibleMeds ® with known, possible or conditional risk for torsade de pointes were evaluated from 2000 to 2020. The German drug prescription report was used as source for defined daily dose‐ (DDD‐) based prescriptions of the German outpatient drug prescription market of the public health insurance system. German SmPCs and US PI of 253 CredibleMeds ® ‐listed drugs were evaluated for contents regarding QT interval prolongation. Results: Of the drugs currently listed on CredibleMeds ®, 59.7% (95% confidence interval [CI] 53.5–65.5%) were listed after 2012. Due to newly listed drugs, the proportion of DDDs of CredibleMeds ® drugs among all prescriptions increased from 4.6% in 2013 to 21.1% in 2019. DDD‐based usage of the CredibleMeds ® drugs already listed in 2013 was similar in 2019. Among the drugs with known QT risk according to CredibleMeds ®, 7.5% (95% CI 2.6–19.9%) of German SmPCs and 21.1% (95% CI 11.1–36.3%) of US PI had no mention of QT issues whatsoever. Conclusion: A significant proportion of all drugs prescribed in the outpatient sector is associated with QT risks according to CredibleMeds ® . SmPCs and PI should systematically be evaluated for concordance with the widely used CredibleMeds ® database to increase medication safety.